The complete mitochondrial genome of Periphyllus koelreuteriae (Takahashi, 1919) (Hemiptera: Aphididae: Chaitophorinae) - Cailing Li; Hao Liu; Liyun Jiang; Gexia Qiao; Jing Chen (Mitochondrial DNA. Part B. Resources)
We sequenced the complete mitochondrial genome of the aphid Periphyllus koelreuteriae. It is 16,828 bp long and includes 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosome RNA genes (rRNAs), a control region, and a repeat region. The control region contains a 273-bp repeat motif repeated 2.3 times. The species-specific repeat region between trnE and trnF comprises two 340-bp repeat units. The maximum-likelihood tree based on all 37 mitochondrial genes indicated a close relationship between P. koelreuteriae and Periphyllus diacerivorus. This study provides a valuable mitogenomic resource for future research on Chaitophorinae phylogeny and P. koelreuteriae diversification.